Pengembangan Plugin Eduplayer pada E-Learning untuk Meningkatkan Kompetensi Animasi Mahasiswa - Afis Pratama (Joined Journal (Journal of Informatics Education), 2020)
E-learning has been widely used in the world of education today because it can be used to help the process of transforming the paradigm of learning from teacher-centered to student-centered. In addition, e-learning has features that teachers can use to support learning activities such as video streaming, virtual laboratory, virtual library, self assessment and so on. In practice-based courses, the use of video tutorials on e-learning is considered necessary as an alternative learning resource. This is because video tutorials are able to display certain lessons repeatedly according to the user's wishes. The short-term goal in this study is to make a decent video tutorial as an alternative learning resource in Graphic Design course, where the tutorial video that has been created will be pinned on e- learning IKIP Veteran Central Java and is expected to improve students' understanding after using video tutorial contained in e-learning. The long-term goal of this research is to be able to create various video tutorials on e-learning in other courses that are practice-based and enrich the content of e-learning itself. The result of this research shows that the students are very interested with the video tutorial on IKIP Veteran e-learning and the tutorial video is also able to improve student learning outcomes.